2017
DOI: 10.1002/cphc.201700775
|View full text |Cite
|
Sign up to set email alerts
|

Flow‐Pattern Characterization of Biphasic Electrochemical Cells by Magnetic Resonance Imaging under Forced Hydrodynamic Conditions

Abstract: The fluid dynamics of a liquid|liquid system inside a four-electrode electrochemical cell were studied by velocimetry magnetic resonance imaging (MRI) and flow propagator measurements. To characterize this system fully, three different cell configurations operating at two rotational frequencies were analyzed. Quantitative information about the stability of the liquid|liquid interface and the dynamics of the organic phase were determined. The NMR spectroscopy results were in agreement with the electrochemical m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 59 publications
0
3
0
Order By: Relevance
“…Second, we have previously shown by means of velocity MRI experiments that rotational speeds above 62 Hz lead to the formation of vortices and the fluid dynamics within this cell deviate from ideal behavior. 15,16 In particular, the velocity profile in the z direction shows that the velocity of the fluid going from the bulk reservoir to the electrode surface increases with rotational speed, but the streamlines lose the homogeneous and parallel distribution because of the formation of vortices, as shown in Figure 7. It can be observed that at high rotational speeds, the material does not arrive to the metal surface in a homogeneous way, with faster dynamics in the borders of the rod and slower velocities in the center, in concordance with previous results.…”
Section: Acs Omegamentioning
confidence: 99%
See 1 more Smart Citation
“…Second, we have previously shown by means of velocity MRI experiments that rotational speeds above 62 Hz lead to the formation of vortices and the fluid dynamics within this cell deviate from ideal behavior. 15,16 In particular, the velocity profile in the z direction shows that the velocity of the fluid going from the bulk reservoir to the electrode surface increases with rotational speed, but the streamlines lose the homogeneous and parallel distribution because of the formation of vortices, as shown in Figure 7. It can be observed that at high rotational speeds, the material does not arrive to the metal surface in a homogeneous way, with faster dynamics in the borders of the rod and slower velocities in the center, in concordance with previous results.…”
Section: Acs Omegamentioning
confidence: 99%
“…We have proved that velocity MRI is a useful tool to characterize the velocity profiles that take place in the interior of a rotating disk electrode (RDE) cell. Electrochemical cells with a RDE configuration are widely used to characterize electrochemical reactions. It can be used to measure the stoichiometric number of electron transfer in the electrochemical reaction, bulk concentration and diffusion coefficient, reaction kinetic constant and reaction intermediates in studying electrode reaction kinetics and mechanisms. RDE is easy to construct with a variety of electrode materials, and it is amenable to rigorous theoretical treatment.…”
Section: Introductionmentioning
confidence: 99%
“…The cell rotation is driven by a 0.5 HP triphasic engine whose rotational frequency and acceleration rates were controlled by a Sinamics G110 frequency inverter (Siemens) that can be either manually or remotely operated [38]. For transient flow experiments, the frequency inverter was triggered with a TTL signal from the NMR console, thus being synchronized with the MRI acquisition.…”
Section: Couette Cellmentioning
confidence: 99%